Faktor Determinan Pembentuk Perilaku Orang Tua dalam Upaya Pencegahan Penyalahgunaan Narkoba oleh Remaja - Lisdahayati, Lisdahayati; Rustiati, Nelly; Yunike, Yunike; Kusumawaty, Ira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the factors that most influence the formation of the role of parents in preventing teenagers from falling into drug abuse. The research method used in this research is an analytical method with a cross-sectional design. The research results show that knowledge about drugs and attitudes towards drug abuse are the factors that have the most influence on the formation of drug abuse prevention behavior in adolescents. In conclusion, a good level of knowledge about drug abuse will still be followed by positive drug prevention behavior; attitudes towards drug abuse have a significant relationship and influence the existence of drug abuse behavior by teenagers. Keywords: Drugs, Drug Abuse, Mother's Attitude, Adolescents